Continuous wave ultrasonic Doppler tomography - Liang, Haidong-Dong (The Royal Society, 2011)
In continuous wave ultrasonic Doppler tomography (DT), the ultrasonic beam moves relative to the scanned object to acquire Doppler-shifted frequency spectra which correspond to cross-range projections of the scattering and reflecting structures within the object. The relative motion can be circular or linear. These data are then backprojected to reconstruct the two-dimensional image of the object cross section. By using coherent processing, the spatial resolution of ultrasonic DT is close to an order of magnitude better than that of traditional pulse-echo imaging at the same ultrasound frequency.